Assessment of the level of quality of nursing care in an infectious diseases ward - Sierpińska, Lidia; Domagała, Monika (Journal of Education, Health and Sport, 2022)
Introduction. An important aspect of the market-based health care system is the provision of a high level of medical services, including the quality of nursing care. In order to provide high quality patient care the subjective and objective methods were applied, as well as assessment tools. Objective. The aim of the study was an objective assessment of the quality of nursing care provided to patients in the infectious diseases ward. Materials and Method. The study was conducted in 2017, and included 105 patients treated in the infectious diseases ward at the Independent Public Teaching Hospital No. 1 in Lublin, Poland. The research method was a diagnostic survey; the techniques: a questionnaire and participant observation; the tool: a standard BOHIPSZO questionnaire according to H. Lenartowicz. Results. A very high coefficient of the quality of nursing care in the infectious diseases ward concerned therapeutic-nursing procedures (99%), and hotel services including satisfaction of existential needs and objectification of a patient (97% each), followed by protection of patients against infection (96%), patient safety (94%), and preparation of patients to self-care before discharge home (92%). A high coefficient of provided care concerned the standard of organization and documentation of nursing care (80%). The provision of information for patients in the infectious diseases ward was assessed by patients in the lowest terms – the care coefficient was 71%. The global coefficient of the quality of nursing care in the infectious diseases ward was on the level of 90.75% of the desired status. The deficit of care (9.25%) was insignificant; p>0.05. Conclusions. The results of the study confirmed that a global coefficient of the quality of nursing care in the infectious diseases ward was on a very high level. Care deficit was insignificant. The improvement of the quality of care in the infectious diseases ward should concern mainly the standard of provision of information to patients, and the organization and documentation of nursing care.